Explicit and implicit teaching Persian language structures and editing methods and translation performance of Iranian undergraduate translation students. (25th July 2019) - Vasheghani Farahani, Mehrdad; Rezaei, Omid; Masoomzadeh, Milad
Abstract : Purpose: The purpose of this paper (experimental–comparative research) is to investigate the possible impacts of explicit and implicit teaching Persian structures and editing methods on the translation performance of the Iranian undergraduate translation students. Design/methodology/approach: This research enjoyed a quasi-experimental design. A quasi-experimental research design was used in this research, as it was impossible to assign random sampling to the subjects. In addition, this research was a comparative group study as there were two experimental groups with two different treatments and one control group with placebo. Table I represents the design of the research. Findings: The results showed that before the treatment there were no significant differences between three groups in terms of translation performance; however, after treatment, the results indicated a statistically significant difference between two experimental groups and treatment group. Moreover, explicit instruction yielded more positive results than the implicit group. Originality/value: Although research in the field of translation assessment and quality in relation to target language are prevalent and in spite of the abundance of research in the field of implicit/explicit instructions in second language teaching and learning, there is no research (to the best knowledge of authors) which looks at translation performance from teaching structures and editing methods of target language perspective with the focus of explicit and implicit (in an English–Persian context).